Estimation of the catchability coefficient of purse seine using split beam echo sounders - Zakaria, M Z; Samo, K B; Hermawan, M; Ambak, M A (Indian Journal of Fisheries, 2011)
This paper aims to estimate the catchability coefficient of purse seine net by comparing the fish abundance estimated through acoustic technique by using split beam echo sounders and the true catch. The fish were caught in the coastal waters around Pulau Kapas, Kuala Terengganu within 0512.04’ to 05Â°19.38’N latitude and 103Â°13.95’ to 103Â°19.53’E longitude using a purse seine boat with 15 m length operating a net with head rope of 256 m in length, 88 m depth and with mesh size of 24.5 mm. Based on six successful experimentations, the catchability coefficient obtained ranges from 0.84 to 0.98. Ox-eye scad (Selar boops) was the most abundant species caught followed by Indian mackeral (Rastrelliger kanagurta).